2016
DOI: 10.1111/febs.13648
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the ‘Fingers’ subdomain of the deubiquitinase USP1 modulate its function and activity

Abstract: Ubiquitin-specific protease (USP)1 is a member of the USP family of deubiquitinating enzymes. Efficient USP1 activity requires binding to its cofactor USP1-associated factor 1 (UAF1), and the USP1-UAF1 deubiquitinase complex has important roles in regulating DNA damage-related processes. USPs show common folding of their catalytic domain, with three subdomains termed Thumb, Palm, and Fingers. The Fingers subdomain appears to be the primary site for ubiquitin binding. In USP1, the Fingers subdomain also mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…It is noteworthy that downregulation of two other representative enzymes from our screen, USP11 and OTUB2, in mouse muscles also blocked Akt deubiquitination in vivo, further exemplifying the validity of our DUB scan approach and the physiological relevance of our findings (Fig EV1C-E). Similar results were obtained when we inhibited USP1 by the electroporation of a GFP-tagged USP1 dominant-negative encoding plasmid (USP1 (C90S) ) [35], which lacks the catalytic cysteine and thus can bind substrates but cannot deubiquitinate them ( Fig 1G). Immunoprecipitation of Akt from USP1 (C90S) -expressing muscles from fasted mice, and analysis of protein precipitates by SDS-PAGE and immunoblotting using anti-K63-linked ubiquitin chains antibody revealed that in the muscles lacking functional USP1 (expressing USP1 (C90S) ) Akt accumulated as K63-ubiquitinated protein ( Fig 1G).…”
Section: Usp1 Is a Deubiquitinating Enzyme For Aktsupporting
confidence: 80%
See 1 more Smart Citation
“…It is noteworthy that downregulation of two other representative enzymes from our screen, USP11 and OTUB2, in mouse muscles also blocked Akt deubiquitination in vivo, further exemplifying the validity of our DUB scan approach and the physiological relevance of our findings (Fig EV1C-E). Similar results were obtained when we inhibited USP1 by the electroporation of a GFP-tagged USP1 dominant-negative encoding plasmid (USP1 (C90S) ) [35], which lacks the catalytic cysteine and thus can bind substrates but cannot deubiquitinate them ( Fig 1G). Immunoprecipitation of Akt from USP1 (C90S) -expressing muscles from fasted mice, and analysis of protein precipitates by SDS-PAGE and immunoblotting using anti-K63-linked ubiquitin chains antibody revealed that in the muscles lacking functional USP1 (expressing USP1 (C90S) ) Akt accumulated as K63-ubiquitinated protein ( Fig 1G).…”
Section: Usp1 Is a Deubiquitinating Enzyme For Aktsupporting
confidence: 80%
“…The shRNA oligo against USP1, USP11, OTUB2 (Table EV2), and Lacz was designed using Invitrogen's RNAi designer tool and was cloned into pcDNA 6.2-GW/EmGFP-miR vector using Invitrogen's BLOCK-iT RNAi expression vector kit. The GFP-tagged USP1 (C90S) dominant-negative encoding construct has been described previously [35]. The mammalian expression vector encoding the C-terminal proline-rich domain of Dab2 was obtained from Dr. Philip Howe (Cleveland Clinic Lerner College of Medicine, Ohio, USA) [50], and the ones encoding HA-tagged PHLPP1 and SFBtagged UAF1 were from Dr. Maddika Subbareddy (CDFD, India) [56].…”
Section: Plasmid Dna and Generation Of Shrnamentioning
confidence: 99%
“…Similar results were obtained when we inhibited USP1 by a different approach, i.e. by the electroporation of a GFP-tagged USP1 dominant negative encoding plasmid (USP1 (C90S) ) (Olazabal-Herrero et al, 2016), which lacks the catalytic cysteine and thus can bind substrates but cannot deubiquitinate them ( Fig. 1F).…”
Section: Usp1 Is a Deubiquitinating Enzyme For Aktsupporting
confidence: 80%
“…The shRNA oligo against USP1 (Table S2) and Lacz were designed using Invitrogen's RNAi designer tool and were cloned into pcDNA 6.2-GW/EmGFP-miR vector using Invitrogen's BLOCK-iT RNAi expression vector kit. The GFP-tagged USP1 (C90S) dominant-negative encoding construct has been described previously (Olazabal-Herrero et al, 2016). The mammalian expression vector encoding the C-terminal proline rich domain of Dab2 was obtained from Dr. Philip Howe (Cleveland Clinic Lerner College of Medicine, Ohio, USA) (Hocevar et al, 2005), and the one encoding SFB-tagged UAF1 were from Dr. Maddika Subbareddy (CDFD, India) (Gangula and Maddika, 2013).…”
Section: Plasmid Dna and Generation Of Shrnamentioning
confidence: 99%
“…Also, USP1-dependent regulation of other signaling pathways such as AKT ( Zhang et al., 2016 , Zhiqiang et al., 2012 ) or upstream elements of the DDR, such as CHK1, a key kinase involved in DDR and DNA repair, which is also stabilized by USP1 ( Guervilly et al., 2011 ), may affect the DDR output together with γ-H2AX formation ( Bozulic et al., 2008 , Surucu et al., 2008 , Xu et al., 2010 ). Owing to the complexity of DDR signaling and multi-layer actions of USP1, there may also be dual and time-/concentration-/cell-system-dependent effects on γ-H2AX formation or on DDR in general, as an induction of γ-H2AX upon USP1 inhibition has also been observed ( Olazabal-Herrero et al., 2016 ). Our results suggest that the genetic and pharmacological suppression of USP1 in rodent β-cell and human islets protected the cells from DNA-damage-induced cell death with preserving β-cell insulin secretion and β-cell key maturation genes, proposing the critical function of USP1 in the regulation of β-cell apoptosis under different diabetogenic conditions.…”
Section: Discussionmentioning
confidence: 99%